FLYWHEEL AS THE KINETIC ENERGY STORAGE IN A GENERATOR SYSTEM: EXPERIMENTAL AND SIMULATION - Tetuko, Anggito Pringgo; Juliyana, Ujang T; Purwanto, Budi A; Kurniawan, Candra; Setiadi, Eko A; Andrameda, Yurian A; Ginting, Masno; Sebayang, Perdamean (Teknologi Indonesia, 2018)
In this paper, a flywheel generator system as a kinetic energy storage was analysed that consists of both theoretical models (analytical and numerical) and experimental. The analytical model was solved to calculate the kinetic energy stored and the moment of inertia of the flywheel. On the other hand, the numerical model was developed to analyse the stress and the deformation distributions on the flywheel. The experiments were conducted by varying the flywheel mass of 15-18 kg; and the pulley ratio of 1:1, 2:1, 3:1. The numerical simulation confirmed that the stress and the deformation values on the flywheel were under the material ultimate stress. The experimental results suggested that the increase of the flywheel mass also increases the capability of the flywheel to store the kinetic energy. A similar trend also found in the pulley ratio variations where the increase of the pulley ratio enhances the rotational speed of the generator thus increasing its electricity generation.